Isolating the "Tech" from EdTech: Experimental Evidence on Computer Assisted Learning in China - Robert W. Fairlie; Prashant Loyalka; Scott Rozelle; Yue Ma (Institute of Labor Economics (IZA), 2020)
EdTech which includes online education, computer assisted learning (CAL), and remote instruction was expanding rapidly even before the current full-scale substitution for in-person learning at all levels of education around the world because of the coronavirus pandemic. Studies of CAL interventions have consistently found large positive effects, bolstering arguments for the widespread use of EdTech. However CAL programs, often held after school, provide not only computer-based instruction, but often additional non-technology based inputs such as more time on learning and instructional support by facilitators. In this paper, we develop a theoretical model to carefully explore the possible channels by which CAL programs might affect academic outcomes among schoolchildren. We isolate and test the technology-based effects of CAL and additional parameters from the theoretical model, by designing a novel multi-treatment field experiment with more than four thousand schoolchildren in rural China. Although we find evidence of positive overall CAL program effects on academic outcomes, when we isolate the technology-based effect of CAL (over and above traditional pencil-and-paper learning) we generally find small to null effects. Our empirical results suggest that, at times, the "Tech" in EdTech may have relatively small effects on academic outcomes, which has important implications for the continued, rapid expansion of technologies such as CAL throughout the world.
Keywords: I21; O15; 330; pencil effects; ICT; EdTech; computer-assisted learning; student learning; educational productivity; RCT